The Management of Scientific Integrity within Academic Medical Centers The Grey Zone between Right and Wrong - Snyder, Peter; Snyder, Peter; Mayes, Linda C.; Smith, William E. (Elsevier Science, 2015)
The Management of Scientific Integrity within Academic Medical Centers discusses the impact scientific misconduct has in eight complex case studies. Authors look at multifaceted mixtures of improper behavior, poor communication, cultural issues, adverse medical/health issues, interpersonal problems and misunderstandings to illustrate the challenge of identifying and managing what went wrong and how current policies have led to the establishment of quasi legal processes within academic institutions. The book reviews the current global regulations and concludes with a section authored by a US federal court judge who provides his perspective on the adequacy of current regulations and policies.Shows how complex most scientific integrity cases are, and how little is clear cut in the adjunction of eachDiscusses how timely and important scientific misconduct is, and its impact on science at largeReviews the current regulations and policies that guide how we manage scientific integrity Examines this complexity in 8 anonymous case studiesConcludes with a section authored by an expertly qualified federal court judge